THE ROLE OF SPIRITUAL LEADERSHIP IN IMPROVING JOB COMMITMENT, ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND EMPLOYEE PERFORMANCE - Idawati, Khoirotul; Mahadun, Hanifudin (Jurnal Aplikasi Manajemen, 2022)
This study aims to examine spiritual leadership affects organizational citizenship behavior (OCB), investigate the effect of spiritual leadership to employee performance, investigate the effect of job commitment to employee performance, to investigate the effect of spiritual leadership to job commitment, to investigate the effect of job commitment to OCB, and to examine the effect of OCB to employee performance of Islamic banking. Related to the research objective, the type of research is explanatory research. The sampling technique was saturated sampling. The sample of the study was 102 employees of Islamic banking in Malang. Questionnaires collected data and analyzed using structural equations modeling (SEM). The results show that spiritual leadership affects OCB. Spiritual leadership effect on job commitment and employee performance. Likewise, job commitment brings no effect on employee performance. Job commitment significantly affects OCB, and OCB affects employee performance. The findings from this research could be applied to enhance employee performance by developing job commitment and organizational citizenship behavior among employees in Islamic banking.